Adding Value to Banana Farming through Production Quality, Post-Harvest Processing, and Access to Local Markets in Regencies of East Java - Donny Ivan Samuel Simatupang; Ni Luh Sri Suryaningsih; Asman Asman; Muhammad Ali Hasim Asyari (Westscience Press, 2026)
Banana farming represents an important agricultural activity that contributes to rural economic development and farmers’ livelihoods in Indonesia. However, many smallholder banana farmers continue to face challenges in maximizing economic value due to inconsistent production quality, limited post-harvest processing capabilities, and restricted access to profitable markets. This study aims to analyze the influence of production quality, post-harvest processing, and access to local markets on value creation in banana farming across regencies in East Java. This research employed a quantitative approach involving 100 banana farmers as respondents. Data were collected using a structured questionnaire measured with a five-point Likert scale and analyzed using Statistical Package for the Social Sciences (SPSS) version 25. The data analysis included validity testing, reliability testing, descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results indicate that production quality, post-harvest processing, and access to local markets have positive and significant effects on value creation in banana farming. Production quality has a significant influence, post-harvest processing contributes positively, and access to local markets demonstrates the strongest effect. The coefficient of determination shows that the research model explains 62.7% of the variation in agricultural value creation. These findings indicate that increasing banana farming competitiveness requires an integrated strategy involving quality improvement, processing innovation, and stronger market connectivity. This study provides practical implications for farmers, agricultural institutions, and policymakers in developing sustainable and value-oriented banana agribusiness systems in East Java.